Origin of magnetic properties in carbon implanted ZnO nanowires - Wang, Y. F.; Shao, Y. C.; Hsieh, S. H.; Chang, Y. K.; Yeh, P. H.; Hsueh, H. C.; Chiou, J. W.; Wang, H. T.; Ray, S. C.; Tsai, H. M.; Pao, C. W.; Chen, C. H.; et al. (NATURE PUBLISHING GROUP, 2018)
Various synchrotron radiation-based spectroscopic and microscopic techniques are used to elucidate the room-temperature ferromagnetism of carbon-doped ZnO-nanowires (ZnO-C:NW) via a mild C+ ion implantation method. The photoluminescence and magnetic hysteresis loops reveal that the implantation of C reduces the number of intrinsic surface defects and increases the saturated magnetization of ZnO-NW. The interstitial implanted C ions constitute the majority of defects in ZnO-C:NW as confirmed by the X-ray absorption spectroscopic studies. The X-ray magnetic circular dichroism spectra of O and C K-edge respectively indicate there is a reduction in the number of unpaired/dangling O 2p bonds in the surface region of ZnO-C:NW and the C 2p-derived states of the implanted C ions strongly affect the net spin polarization in the surface and bulk regions of ZnO-C:NW. Furthermore, these findings corroborate well with the first-principles calculations of C-implanted ZnO in surface and bulk regions, which highlight the stability of implanted C for the suppression and enhancement of the ferromagnetism of the ZnO-C:NW in the surface region and bulk phase, respectively.
Keywords: RAY-ABSORPTION SPECTROSCOPY; ELECTRONIC-STRUCTURE; NANOSTRUCTURES; FERROMAGNETISM; SEMICONDUCTORS; BACKSCATTERING; MICROSCOPY; EMISSION; VACANCY